Microphysical retrieval in severe storms from ground-based and space-borne radar network: application to La Plata region in South America - Arias Hernández, Iván D., author; Chandrasekar, V., advisor; Cheney, Margaret, committee member; Ray, Indrakshi, committee member; Chávez, José, committee member (Colorado State University. Libraries, 2023)
The microphysics of severe weather is studied using a network approach from multiple platform observations. Observations acquired near the foothills of the Andes in Argentina are used in this investigation. La Plata region in Argentina is known for having some of the tallest storms on Earth. During the Austral summer of 2018, a network of radars was deployed in this region to study these storms as part of the RELAMPAGO field experiment. This network of ground-based radars, in addition to satellite and in-situ observations, is used to understand the microphysics of severe storms in this part of the world. The knowledge gained from studying the microphysics of these storms in South America is applied to understand convection more broadly. In addition, these multiple platform observations are used to understand how the storms in South America may differ from storms in other regions. The analysis from simultaneous radar observations is used to self-calibrate the radar network. In this investigation, first, an extensive calibration of the radar network measurements was performed to obtain high-quality data for this study. The ground-based radars' dual-polarization measurements were calibrated using a network-based approach. In addition, satellite measurements from GPM radar were used as a common platform for calibrating the ground-based radars in the network. A new parameterization for the attenuation correction is developed for ground-based radar in this region as an outcome of the network calibration exercise. After careful calibration, the radar measurements in the network were used to obtain observational statistics over the RELAMPAGO campaign domain. These statistics are applied to understand the connection between the radar retrievals and to select the severe weather cases to study. For the severe weather cases identified in the radar statistics, spectral polarimetric decomposition from radar signal samples in updraft environments is derived. First, updrafts are identified using dual Doppler analysis. Subsequently, the reflectivity, differential reflectivity, and coherence spectra are computed from radar signal samples. Practical considerations about the computation of the spectrum in updraft are also presented. The spectral analysis revealed that bimodalities in the spectrum can be found in updraft conditions. In addition, a technique to quantify the attenuation of C-band radar signals in melting ice was developed using multiple radar observations. The attenuation estimates are used to parameterize the specific attenuation in melting ice to explain the enhanced attenuation. Finally, convective permitting high-resolution simulations are compared with the radar network observations for a representative severe weather case. This comparison is conducted to test the effectiveness of downscaling to resolve better convective processes that lead to severe weather.
Keywords: dual polarization radar; microphysics; spectrum; GPM; attenuation; NWP